Wpływ specjalnych stref ekonomicznych na rozwój społeczno-gospodarczy małych miast Polski - Hajduga, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article describes special economic zones and their function within Polish small cities. Special economic zones (SEZ) are governmental instruments affecting national economy. The Polish special zones are generally distributed all over the country. The main aim of this paper is a presentation of an important role of special economic zones in development of Polish cities and economic activation of regions. The first part of the paper discusses different definitions, purposes, premises and functions of SEZs. Then the author describes Special Economic Zone of Kamienna Góra and of Special Economic Zone Kostrzyn-Słubice and also shows benefits of their activity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 288-300